The Influence of Teacher Performance on the Learning Achievement of Grade XI Students of the Office Department of SMK Negeri 1 Baubau - Suci Nur Islam; Haedar Akib; Sirajuddin Saleh (Journal of Educational Development and Learning (JEDAL), 2025)
Teacher performance plays a central role in shaping the quality of education, and a deeper understanding of this relationship is key to improving the education system. By knowing the direct impact of teacher performance, this research can also increase teacher accountability, encourage the development of more effective teaching strategies, and contribute to efforts to increase equality in the achievement of learning outcomes. The research used a quantitative descriptive method involving 59 out of a total of 139 students, selected by random proportional technique. Collect data by observation, questionnaire, and documentation, then analyze with the SPSS 25 program. Validity testing, reliability testing, data normality testing, product moment correlation analysis, descriptive data analysis methods, and basic linear regression analysis are all used in the analysis. The results of the study showed that the performance of teachers was categorized as good as seen from the indicators of the ability to plan, implement, evaluate and follow up on learning. Similarly, the average level of student learning achievement is assessed based on aspects of knowledge and skills or expertise. A correlation value of 0.294 showed that there was a 29.4% relationship between student learning achievement and teacher performance. The coefficient of determination, which stands at 0.087, shows that there is an impact of 8.7% of teacher performance on student learning achievement. At SMK Negeri 1 Baubau, teacher achievement has a minimal beneficial impact on student progress, but it is not statistically significant. It is possible to conclude from the findings of the study that there are various factors/causes that affect student learning achievement but are not covered in this study